2011
DOI: 10.1037/a0024552
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious moral licensing: The influence of others' past moral actions on moral behavior.

Abstract: This article investigates the effect of others' prior nonprejudiced behavior on an individual's subsequent behavior. Five studies supported the hypothesis that people are more willing to express prejudiced attitudes when their group members' past behavior has established nonprejudiced credentials. Study 1a showed that participants who were told that their group was more moral than similar other groups were more willing to describe a job as better suited for Whites than for African Americans. In Study 1b, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
162
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(180 citation statements)
references
References 49 publications
(80 reference statements)
15
162
2
1
Order By: Relevance
“…This suggests that people may feel licensed to behave in a racist way when their in-group behaves in a nonracist way in a similar context. There are, however, some differences between our study and that of Kouchaki (2011). Therefore, our article adds to the literature in the following ways: First of all, the present research will study vicarious licensing and cleansing through close others in the moral domain of environmentally friendly behavior, because understanding the factors that influence people's environmentally friendly behaviors is a first step in inducing long-lasting environmentally friendly behaviors (Bratanova, Loughnan, & Gatersleben, 2012;Schmuck & Schultz, 2002).…”
Section: Vicarious Licensing and Vicarious Cleansingmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that people may feel licensed to behave in a racist way when their in-group behaves in a nonracist way in a similar context. There are, however, some differences between our study and that of Kouchaki (2011). Therefore, our article adds to the literature in the following ways: First of all, the present research will study vicarious licensing and cleansing through close others in the moral domain of environmentally friendly behavior, because understanding the factors that influence people's environmentally friendly behaviors is a first step in inducing long-lasting environmentally friendly behaviors (Bratanova, Loughnan, & Gatersleben, 2012;Schmuck & Schultz, 2002).…”
Section: Vicarious Licensing and Vicarious Cleansingmentioning
confidence: 99%
“…This effect may be referred to as vicarious moral licensing (cf. Kouchaki, 2011). In contrast, if a close other behaves in a morally questionable manner, people may be subsequently more likely to behave relatively morally.…”
Section: Vicarious Licensing and Vicarious Cleansingmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Goldstein and Cialdini (2007) found that participants perceived themselves as more caring, sympathetic, and helpful after they observed another person with whom they felt a strong sense of merged identity offering help, again providing evidence that people mentally share the traits of a close other. Furthermore, the heightened sense of the self-other collective also gives people access (actual or illusory) to desirable outcomes of close others, such as information, consumption, knowledge, moral credentials, and success (Kouchaki 2011;Tesser 1988;Tu and Fishbach 2015;Wegner 1987;Wegner, Erber, and Raymond 1991).…”
Section: Interpersonal Closeness: When You and I Become "We"mentioning
confidence: 99%
“…So far, mainly fi nancial drivers have been taken into account and research has just begun to (Kouchaki, 2011), we suggested that an individual's moral load can be reduced as well through optimistic beliefs regarding the problem-solving capacity of green technology in a society as a whole. Hence, we hypothesized that optimism in green technology weakens the individual's felt responsibility to act pro-environmentally.…”
Section: Introductionmentioning
confidence: 99%